2013
DOI: 10.1159/000356695
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Macular Degeneration Screening Using a Nonmydriatic Digital Color Fundus Camera and Telemedicine

Abstract: Purpose: To investigate the use of a nonmydriatic digital color fundus camera and telemedicine as screening tools for age-related macular degeneration (AMD). Methods: Nonmydriatic color fundus photography was performed on patients consulting health examination centers and transmitted by telemedicine to an ophthalmology department. Rates for different grades of AMD were calculated and also statistically related to the presence or absence of risk factors. Results: Among the 1,022 patients screened, a total of 1,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 13 publications
0
21
1
Order By: Relevance
“…For example, pediatric teleophthalmology (retinopathy of prematurity [ROP] screening), [5][6][7] focused glaucoma screening programs, [8][9][10] and macular degeneration screening. 11,12 Data on all of these programs suggest that teleophthalmology is effective, safe, and well accepted by patients. 13,14 Given the safety and success of teleophthalmology to detect eye disease other than DR, the Veterans Health Administration (VA) is contemplating utilizing more teleophthalmology to help address access issues and provide care for its growing population of geriatric (age 65+) and rural Veterans; projected to grow 66-132% in the next 10-15 years.…”
Section: Introductionmentioning
confidence: 99%
“…For example, pediatric teleophthalmology (retinopathy of prematurity [ROP] screening), [5][6][7] focused glaucoma screening programs, [8][9][10] and macular degeneration screening. 11,12 Data on all of these programs suggest that teleophthalmology is effective, safe, and well accepted by patients. 13,14 Given the safety and success of teleophthalmology to detect eye disease other than DR, the Veterans Health Administration (VA) is contemplating utilizing more teleophthalmology to help address access issues and provide care for its growing population of geriatric (age 65+) and rural Veterans; projected to grow 66-132% in the next 10-15 years.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, telemedicine-based screening of diabetic retinopathy (DR) has been shown to increase the proportion of patients receiving an annual exam, identify diabetic changes to the retina, and decrease vision loss from DR at a population level [3,4,5]. Several studies have evaluated telemedicine for glaucoma and age-related macular degeneration as well [6,7,8,9]. Results have been mixed but promising for both conditions.…”
Section: Introductionmentioning
confidence: 99%
“…In the next figure there is list of all the different components usually present in teleglaucoma screening. We can find also telescreening studies in retinopathy of prematurity (Lorenz et al 2009;Quinn et al 2014;Richter et al 2009) and in age-related macular degeneration (Bats et al 2014;Duchin et al 2015). Teledermatology is one of the most developed fields in telemedicine.…”
Section: The Role Of Telemedicine In Screeningmentioning
confidence: 79%
“…Several studies have confirmed that the clinical outcome is better if patients with diabetes are screened and treated early, saving years of vision and reducing societal costs (Ciulla, Amador, and Zinman 2003;Mohamed, Gillies, and Wong 2007). AMD screening programs are receiving great interest in the last years with the first implementations showing its effectiveness in reducing the number of patients with blindness although presenting discrepancies in the cost-effectiveness of these methods (Bats et al 2014;Chan et al 2015;Tamura et al 2015).…”
Section: Benefits and Disadvantages Of Screeningmentioning
confidence: 99%
See 1 more Smart Citation